DIAGNOSTICS AND OPTIMISATION OF BUSINESS PROCESSES WITHIN STATE SUPPORT FOR SAFE AND SUSTAINABLE STRATEGIC DEVELOPMENT OF EXPORT-ORIENTED PRODUCERS (INNOVATIVE ECONOMY, 2025)
Afanasiev Ye.V., Rtyshchev S.A., Afanasiev I.Ye., Afanaseva M.H.  DIAGNOSTICS AND OPTIMISATION OF BUSINESS PROCESSES WITHIN STATE SUPPORT FOR SAFE AND SUSTAINABLE STRATEGIC DEVELOPMENT OF EXPORT-ORIENTED PRODUCERSPurpose. The article aims to improve the theoretical and methodological approaches to diagnosing and integrated assessment of the economic security level of export-oriented iron ore enterprises in Ukraine. This is achieved through the systematization of functional components, the detailing of indicator systems, and the development of a mechanism for optimizing business processes in the context of sustainable strategic development.Methodology. The research employs methods of economic and mathematical modelling, structural and logical decomposition, rating evaluation, and quantitative analysis of financial and economic indicators. An algorithm for comprehensive monitoring and integration of partial indicators into weighted composite scores is substantiated. The approach covers the following functional components: liquidity and solvency, financial stability, profitability, business activity, product competitiveness, fixed assets condition, and the efficiency of organizational and managerial potential.Findings. A conceptual structural and functional scheme of the mechanism for diagnosing and optimizing business processes of sustainable development of iron ore enterprises is proposed. A system of indicators for each functional component of economic security has been determined, and an algorithm for integrating them into a unified composite indicator has been developed. A step-by-step approach to assessment has been formulated, ensuring the comprehensiveness of monitoring and the reliability of forecasting the financial and economic condition of enterprises.Originality. The methodology of enterprise economic security has further developed by detailing the content of functional components, substantiating their indicator system, and applying integrated weighted assessments. A novel conceptual model of economic and mathematical modelling is proposed, which combines quantitative analysis of indicators with the concept of sustainable strategic management.Practical value. The proposed approach enhances the accuracy of diagnosing and forecasting the economic security of iron ore enterprises, facilitates the optimization of business strategies under uncertainty, and allows managerial decisions to be effectively adapted to modern market transformations. The results can be applied in the practice of corporate integrated structures and individual business entities, as well as by public authorities in shaping policies to support export-oriented producers.Key words: diagnostics; controlling; iron ore enterprise; state support; export products; economic security; business process; economic and mathematical modelling; financial and economic risks; corporate governance.
Keywords: diagnostics; controlling; iron ore enterprise; state support; export products; economic security; business process; economic and mathematical modelling; financial and economic risks; corporate governance